Evaluación formativa y la comunicación oral en niños de la institución educativa inicial N° 713, Yavarí 2024 - Perez Rufino, Belcy (2025)
The purpose of the study was to determine the relationship between the level of formative assessment and oral communication in children from the Initial Educational Institution No. 713, Yavarí, 2024. This study focuses on a quantitative analysis of a relational type, with a non-experimental, descriptive and correlational cross-sectional research design. The sample consisted of 82 children from the initial level of the Initial Educational Institution No. 713, Yavarí. For data collection, the observation technique was used, with an observation guide as an instrument. Both elements were validated by three experts in the area and reliability was determined using the Cronbach Alpha method. The results reveal a Kendall Tau-b correlation coefficient of 0.755 and a significance value of 0.05, indicating a significant correlation between formative assessment and oral communication. Therefore, the null hypothesis is rejected and the general hypothesis is accepted, which maintains that the level of implementation of formative assessment is significantly related to the level of oral communication in children.